2004
DOI: 10.1021/jf035223y
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexation by the Peptide-Bound Maillard Reaction Products Nε-Fructoselysine and Nε-Carboxymethyllysine

Abstract: Although the Maillard reaction between proteins and carbohydrates is of central importance for food processing and in vivo processes, only little is known about changes of the metal-binding properties induced by protein glycation. The purpose of this study was to examine the complex formation of the quantitatively important peptide-bound Maillard reaction products (MRPs) N(epsilon)-fructoselysine and N(epsilon)-carboxymethyllysine with the biologically relevant metal ions copper(II) and zinc(II). The MRPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
3
34
0
2
Order By: Relevance
“…The posttranslational modification of proteins by carbohydrates leads to the formation of new coordination centers for metal ions within a protein chain. But no complexation of Zn (II) with Maillard reaction products Nε fructolysine and Nε carboxymethyl lysine was observed [31]. Similar results of the absence of peak for zinc binding are observed through our FTIR data, except for a new peak at 2,036 cm −1 , indicating presence of hydrogen bond or ionized compound in presence of zinc.…”
Section: Zinc-vitamin Interaction In Albumin Glycationsupporting
confidence: 88%
“…The posttranslational modification of proteins by carbohydrates leads to the formation of new coordination centers for metal ions within a protein chain. But no complexation of Zn (II) with Maillard reaction products Nε fructolysine and Nε carboxymethyl lysine was observed [31]. Similar results of the absence of peak for zinc binding are observed through our FTIR data, except for a new peak at 2,036 cm −1 , indicating presence of hydrogen bond or ionized compound in presence of zinc.…”
Section: Zinc-vitamin Interaction In Albumin Glycationsupporting
confidence: 88%
“…Saxena et al [34] showed that the Cu(II), Ca(II), and Zn(II) binding ability of proteins is related to their carboxymethyllysine content. Studies on metal complexation by the peptide-bound CML show also that post-translational modification of proteins by carbohydrates leads to the formation of new coordination centers for metal ions within a protein chain [35]. The binding of the redox-active metals by proteins can be linked to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Participation of metals in the Maillard reaction and their incorporation into intermediate products is closely related to the biological availability of mineral elements (Delgrado-Andrade, Seiquer, Nieto, & Navarro, 2004;Morales, Fernández-Fraguas, & Jiménez-Pérez, 2005;Sarria & Vaquero, 2001, 2006Seiquer, Valverde, Delgrado-Andrade, & Navarro, 2000;Whitelaw & Weaver, 1989) and the chemical damage caused to some essential amino acids (Leclere, Birlouez-Aragon, & Meli, 2002;Seifert, Krause, Gloe, & Henle, 2004). According to several authors, the amounts of soluble and dialyzable Zn and Fe in model solutions or thermally treated products decreased significantly due to the interaction of reducing sugars and amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…This order differs somewhat from the Irving-Williams order of transition metals complex stability: Mn 2+ < Fe 2+ < Co 2+ < Ni 2+ < Cu 2+ > Zn 2+ (Irving & Williams, 1953), which might suggest the presence of more than one type of ligand. The antioxidant or pro-oxidant activity of melanoidins as chelating agents of metal ions was also described (Leclere et al, 2002;Pokorny, 1991;Seifert et al, 2004;Umetsu, Ikeda, & Nguyen, 1999;Wen et al, 2005). The metal chelating ability of Maillard reaction products, the stability of the complexes formed and the accumulation of chromophores in the reaction systems depend on the type of cations and amino compounds and on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%